Inside Back Cover: Seven‐Step Synthesis of All‐Nitrogenated Sugar Derivatives Using Sequential Overman Rearrangements (Angew. Chem. Int. Ed. 10/2021). Issue 10 (4th January 2021) - Okuyama, Yuya; Kidena, Mayu; Kato, Erina; Kawano, Sayaka; Ishii, Koki; Maie, Kenta; Miura, Kazuki; Simizu, Siro; Sato, Takaaki; Chida, Noritaka
Abstract : All‐nitrogenated sugars (ANSs), in which all hydroxy groups in a carbohydrate are replaced with amino groups, are anticipated to be privileged structures with useful biological activities. In their Communication on page 5193, Takaaki Sato, Noritaka Chida, and co‐workers report the synthesis, transformation, and biological tests of ANS derivatives. The key to success was a seven‐step synthesis of ANSs by a sequential Overman rearrangement enabling formal simultaneous substitution of four or five hydroxy groups in monosaccharides with amino groups.